2014
DOI: 10.1128/mbio.00969-14
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Widely Used Listeria monocytogenes Strains EGD, 10403S, and EGD-e Highlights Genomic Differences Underlying Variations in Pathogenicity

Abstract: For nearly 3 decades, listeriologists and immunologists have used mainly three strains of the same serovar (1/2a) to analyze the virulence of the bacterial pathogen Listeria monocytogenes. The genomes of two of these strains, EGD-e and 10403S, were released in 2001 and 2008, respectively. Here we report the genome sequence of the third reference strain, EGD, and extensive genomic and phenotypic comparisons of the three strains. Strikingly, EGD-e is genetically highly distinct from EGD (29,016 single nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
162
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 190 publications
(170 citation statements)
references
References 86 publications
7
162
1
Order By: Relevance
“…They are thought to promote the cell-to-cell spread of L. monocytogenes by relieving the cortical tension of the host cell and enhancing the ability of the bacterium to protrude into the plasma membrane (52). A fourth type of internalin, which contains an atypical leucine-rich repeat region, has also been recently described (53) with lmo0460 as the sole representative member. The genomes of both strains in this study were examined for the presence of internalin and internalin-like genes.…”
Section: Resultsmentioning
confidence: 99%
“…They are thought to promote the cell-to-cell spread of L. monocytogenes by relieving the cortical tension of the host cell and enhancing the ability of the bacterium to protrude into the plasma membrane (52). A fourth type of internalin, which contains an atypical leucine-rich repeat region, has also been recently described (53) with lmo0460 as the sole representative member. The genomes of both strains in this study were examined for the presence of internalin and internalin-like genes.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its ability to shift quickly between saprophytic growth in the environment and potentially lethal pathogenesis upon contacting a host, L. monocytogenes has been referred to as a bacterial "Dr. Jekyll and Mr. Hyde" (3). The ability to tolerate or thrive in a variety of unfavorable conditions, including high salt, low pH, and refrigeration temperatures, has made L. monocytogenes a formidable challenge to the food industry (1,2). Therefore, it is important to understand the set of factors that enable L. monocytogenes to survive so effectively in a wide variety of inhospitable environments.…”
mentioning
confidence: 99%
“…isteria monocytogenes is a Gram-positive, food-borne, facultative intracellular pathogen that infects a broad range of vertebrate hosts (1,2). The bacterium leads a saprophytic lifestyle in the environment and is commonly found in soil, water, and decaying organic matter.…”
mentioning
confidence: 99%
“…9e11, 15 More than 300 kinds of ncRNA have been found in LM, which include 150 different transencoding small RNA (sRNA) fragments. 16 Small RNA could match the complementary noncontiguous regions of the targeted messenger RNA to regulate the expression of related genes. 17e20 Nielsen et al 21 have found that sRNA LhrA could bind to the 5 0 sequence of chiA messenger RNA, thereby preventing its binding to 30S ribosomes and tRNAf Met and subsequent formation of translation initiation complex, which directly affect the expression of chiA.…”
Section: Discussionmentioning
confidence: 99%